On the optimality of resetting executive stock options - Acharya, Viral V.; John, Kose; Sundaram, Rangarajan K. (Journal of Financial Economics, 2000)
The practice of resetting strike prices on underwater executive stock options has drawn criticism for weakening managerial incentives. Our model shows that although the anticipation of resetting can negatively affect initial incentives, resetting can still be an important, value-enhancing aspect of compensation contracts, even from an ex-ante standpoint. In fact, we find that some resetting is almost always optimal. The relative advantages of resetting diminish with greater ability of managers to influence the resetting process, greater relative importance of external factors on stock performance, and lower costs of replacing incumbent managers.